Mathematical modeling of blood flow and mass transfer in the human cardiovascular system - Diniz, Luíza Wanderley (2019)
The application of transport phenomena concepts combined with medical practice has a positive effect in physiological phenomena comprehension, aiding medical professionals with diagnosis and providing tools to improve treatments. To describe a cardiovascular system from a mechanical and mass transport point-of-view is a effective strategy that can reduce the number of surgical interventions, increase the efficiency of treatments and diagnosis precision. In this study is presented a new approach, from a chemical process point-of-view, for modeling the cardiovascular system. In order to implement and simulate the models the open-source process simulator software EMSO was used. Initially a compartmental macroscopic model (0D) is applied without any component balance. This model is a simplification where space variables are not considered rendering the system only time-variant. This stage was intended to first validate the using of EMSO (Enviroment for Modelling, Simulation and Optimization) for a biological simulation. Afterwards, the multicompartimental physiological based pharmacokinetics model (PBPK) was implemented in order to simulate the drug distribution in the system. The system was divided into several compartments where physiological properties can be considered constants. All parameters were obtained from literature. Qualitative results are presented. The main goal is to study drug disposition in the body by monitoring pressure, flow and concentration. The results for the model implementation checking (using EMSO) were sactisfactory qualitatively, but did not reproduce the literature quantitatively due to the initial conditions. Representative profiles for the variation in time of the concentration of chemical in blood in several vessels and in tissues (kidney and liver) were obtained.